(untitled) (Journal of Naval Architecture and Marine Engineering, 2011)
Automatic hexahedral mesh generation is a very deserving solution for better performance of finite element analysis of complex large structures. At present plastering, whisker weaving and whisker weaving based plastering algorithm are available to perform such tasks. As these hexahedral mesh generation processes are fully automatic, it is possible to form some elements, which don’t have high enough qualities for finite element analysis. For this reason, a reliable post-processing method is presented in this paper which can modify the shapes of the already generated hexahedrons. Four different structural models are tested and the results show that the proposed method can effectively modify the quality of the inverted hexahedrons and eliminate the invalid ones. Keywords: Doublet; triplet; quadruplet; Whisker weaving based plastering algorithm; hexahedral mesh DOI: http://dx.doi.org/10.3329/jname.v8i2.5646 Journal of Naval Architecture and Marine Engineering 8(2011) 121-128